Time‐varying ionosonde trend: Case study of Sodankylä hmF2 data 1957–2014. Issue 8 (13th August 2015) - Roininen, Lassi; Laine, Marko; Ulich, Thomas
Abstract We discuss trend analysis of nonstationary ionosonde hmF2 time series measured at Sodankylä Geophysical Observatory (67.4∘N, 26.7∘E), Finland, 1957–2014. We model the hmF2 with a dynamic regression time series model with the following components: a slowly varying background level, seasonal variations, and solar effects. We analyze the time series with a dynamic linear state space model. Such an approach allows model components to vary in time, allowing us to study the dynamic stochastic nature of the underlying long‐term trend. This feature is lacking in most time series models used in atmospheric and environmental long‐term trend analyses. Our objective is to understand the long‐term hmF2 trend with respect to increased levels of carbon dioxide and methane in the atmosphere. Based on model estimates, this phenomenon is predicted to cool the thermosphere and leads to decrease of the altitude of the so‐called F2 layer peak. After accounting for the effects of solar activity variations on the data, we see that the estimated trend shows an almost 30 km decrease of the F2 layer peak during the observation period. The decrease of the peak during 1990–2010 is significantly greater than during earlier observation period.